The relationship between demographic characteristics, personality traits and users’ seek values in multiple service industries in Saudi Arabia - Alotaibi, Badah Homuod; Al-Matari, Ebrahim Mohammed (MCSER Publishing, Rome-Italy, 2015)
This study is an attempt to examine the relationship between demographic characteristics, personality traits and users’ seek values in multiple service industries in Saudi Arabia.The sample is comprised of 400 sampling where data is obtained through a distributed questionnaire.This study used multiple regressions to test the relationship between independent variables and dependent invariable.The results found that there is a positive relationship between demographic characteristics and users’ seek values.In addition, there is a positive significant association between personality traits and users’ seek values.Finally, this research provided some limitations and suggestions for future researchers at the end of the study. © 2014, Mediterranean Center of Social and Educational Research. All rights reserved.